Review of primary care treatment protocols for hypertension in various states of India - Muthathal Subramanian; Bhushan Dattatray Kamble; Meely Panda; Rashmi Kundapur; Chandralekha Kona (Wolters Kluwer Medknow Publications, 2023)
Over the past few decades, hypertension (HTN) has affected both young and old people. The public health problem has an enormous economic impact on societies as well. The present review aimed to understand and compare the differences from the available literature on HTN treatment at the primary care level in various states and at the national level in India. We reviewed the latest international, national, and state guidelines/protocols available for the treatment of HTN. In addition, we also searched the PubMed database with relevant Medical Subject Headings terms and included the articles published in the last 5 years. A total of 204 articles were screened and finally, eligible 5 articles were included in the review. International guidelines preferred thiazide diuretics as a drug of choice. While the state protocols and national guidelines preferred calcium channel blockers, followed by angiotensin receptor blockers as the drug of choice. All these guidelines focused on low-dose monotherapy. These guidelines also summarized additional drugs required in case of comorbid conditions. However, the new Essential Medicine List published by the World Health Organization prefers low-dose fixed-drug combination (two-drug regimen) at the primary care level for treatment of HTN. There was not much cost difference between monotherapy and fixed-drug regimens based on the published studies. With due rise in HTN cases, the standardized protocol is ubiquitously needed for better application, comparison, and streamline of the program. Fixed-drug combination therapy can be considered for better control rates among hypertensives by improving adherence and efficacy.